Kesesuaian Implementasi Ekonomi Hijau pada Perusahaan Go Green dalam Perspektif Maqashid Syariah - Oktavianur, Andika; Malihah, Lola; Karimah, Husna; Sudirwo, Sudirwo (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2024)
This research aims to find out the general picture of the implementation of the green economy in companies that declare themselves as companies based on a green economy and analyze the implementation of the green economy in companies based on a green economy according to maqashid sharia. This research uses a literature study method (library research). The results of this research show that there is compatibility between the implementation of the green economy according to 5 principles: hifdzu din, hifdzu nafs, hifdzu aql and hifdzu mal. Although in implementation the policy each company carries out different activities. This is focused on go green innovation which is its own focus starting from raw material extraction, production processes to waste management, but all of these are still related to maqashid sharia principles.